Technological properties of montmorillonite modified with lactocin 705, AL705 and nisin. Issue 6 (31st March 2020) - Blanco Massani, Mariana; Fernández, Mariela A.; Molina, Vanesa; Zelaya Soulé, María Emilia; Melian, Constanza; Vignolo, Graciela; Castellano, Patricia; Torres Sánchez, Rosa M.
Abstract: Montmorillonite clay (Mt) was proposed in this work to provide thermal protection of bacteriocins without loss of their functionality. The Mt‐bacteriocins with 0.24 CEC preserved their antimicrobial activity, and their thermal stability was up to 121°C/ 60 min, which allows them to be added to the melt for extrusion during the processing of polymer/antimicrobial films. Then, the release of bacteriocin in contact with water and sunflower oil was evaluated, and it was observed that for Mt‐nisin with 0.60 CEC (Mt‐NisM 0.60) up to 10 days of contact, antimicrobial activity was conserved. In addition, in contact with sunflower oil the Mt‐bacteriocin samples tested retained or exerted their microbiological activity. These results are promising for food packaging applications. This is the first report on the use of Mt to support the bacteriocins produced by Lactobacillus curvatus CRL705. Practical applications: Thermal protection of bacteriocins produced by L. curvatus CRL705 and Lactococcus lactis CRL1109, without loss of their functionality was proposed by loading each of them on montmorillonite (Mt) clay. To attain that objective a bacteriocin amount corresponding to 24% of the CEC of the Mt was loaded, and the release of bacteriocin in contact with water and sunflower oil was evaluated. The microbiological activity of Mt‐bacteriocin samples was conserved when tested in contact with sunflower oil. These results are promising for food packaging applications.